A Mixed Methods Study on the Student Engagement in Online Ideological and Political Course within Higher Vocational Colleges in Anhui Province, China - Sun, Chunxiu (Unimas, 2025)
During the COVID-19 pandemic, ideological and political (I&P) courses in China's higher vocational colleges experienced an unprecedented and rapid shift from traditional face-to-face instruction to remote online teaching. These courses, which focus on value orientation and critical thinking, traditionally rely on interactive and dialogic teaching methods. The move to virtual environments significantly affected both how students engage and the depth of their engagement. To fill the current research gap in this area, this study aims to explore how student engagement in online I&P courses is created, developed, and sustained during and after the pandemic. Guided byActivity Theory (AT), Social Interaction (SOI), and Critical Pedagogy (CP), the study systematically examines how technological tools, power dynamics, and teacher-student interactions influence student engagement. Aconvergent parallel mixed-methods design was employed. Quantitatively, structured surveys were administered to 611 students from the 2019, 2020, and 2021 cohorts in higher vocational colleges in Anhui Province. Qualitatively, in-depth interviews were conducted with 30 representative students to explore their real-life experiences with online learning, platform usage, and value internalization. Findings show no statistically significant differences in engagement levels across academic years. However, the qualitative data revealed several key factors affecting engagement, such as lack of interaction, emotional disconnection, and challenges with platform usability. The combined analysis indicates that clear instructional rules, peer collaboration mechanisms, and contextually appropriate teaching strategies are essential to promote students' cognitive, emotional, and behavioral engagement. Theoretically, this study advances by integrating AT, SOI, and CP into a comprehensive analytical frameworkfor student engagementin ideologicallyfocusededucation.Practically, it offers evidence-based recommendations for improving online I&P course design and promoting deep student engagement in higher vocational education in the post-pandemic era. Keywords: COVID-19 pandemic, ideological and political courses, online learning, mixed-methods, student engagement, higher vocational colleges